STUDY ON THE ABILITY IN IDENTIFYING LOCAL HEALTH PROBLEMS (HIV/AIDS) - Lestari, Tri; Sugiarsi, Sri (JURNAL PROFESI || MEDIA PUBLIKASI PENELITIAN, 2014)
Problems encountered in the prevention and treatment of Â HIV/AIDS in Tasikmadu Karanganyar is the poor ability of the community to identify local health issues (HIV/AIDS). The purpose of this study is to examine and identify the factors related to the ability of communities to identify local health problems in HIV/AIDS in Tasikmadu Karanganyar. The study was observasonal analytic cross sectional design. The population in this study were all health cadres in Puskesmas Tasikmadu Karanganyar. The sample was 90 people taken by cluster random sampling technique. Independent variable was the level of education, access to information, the survey introspective, leadership and the dependent variable was the ability of communities to identify local health issues (HIV/AIDS ). The research instrument was questionnaire used to collect data. The analysis of this study used regression multiple linear. The results showed that the level of education, access to health information, surveys introspective and leadership contributed to the increased capacity of communities to identify local health issues (HIV/AIDS) by 74%. The conclusions in this study is no significant effect simultaneously and education level, access to health information, surveys introspective and leadership to the ability of communities to identify local health issues (HIV/AIDS) at p = 0.000. Â  Keywords: Identification, Health Issues, Local, HIV/AIDS